METHOD (ALGORITHM) FOR A NUMERICAL AND GRAPHIC DETERMINATION OF STIFFNESS IN BENDING OF STRUCTURAL PARTICLEBOARDS (Innovation in Woodworking Industry and Engineering design, 2026)
The algorithm refers to a nomogram for numerical and graphic determination of stiffness in bending of structural particleboards (SPBs). SPBs are technologically formed composite wood-based products with standardised designation P6 with wide application in construction, furniture manufacturing and interior. As evaluation criterion for the load-carrying capacity of the boards, i.e. for their fitness for use in various structural solutions, serves their strain-strength index stiffness in bending St, defined in technical literature as a product of the inertia moment of the cross-section Jy and the modulus of elasticity in bending Em. For the time being, in engineering calculations, only indirect estimates for this index on the basis of the values for the modulus of elasticity in bending are used.The algorithm for numerical and graphic determination of stiffness in bending of SPBs is based on:- the physical nature of the composite as technologically formed layered material and the simulation modelling of its cross-section as a “double T beam”;- the experimentally established empirical dependences of the modulus of elasticity in bending on the bulk densities of the composite board and the wood raw material.